LINGUISTIC AND CULTURAL AFFINITIES: THE CASE OF ARABIC AND ETHIOPIAN LANGUAGES - Dadoo, Yousuf (Journal for Semitics, 2017)
Multi-faceted relations between Ethiopia and South Arabia existed since the sixth century B.C. During the earlier phase, the Christian Ethiopians networked with their co-religionists. Later they interacted primarily with Muslim Arabs some of whom settled in Ethiopia either in search of religious sanctuary or for trade purposes. The Muslims entrenched themselves and established petty kingdoms between the ninth and fifteenth centuries C.E. Thereafter, they suffered huge reversals at the hands of their Christian compatriots who were assisted by the Portuguese colonial power. Over the last two centuries relations between these two religious groups suffered appreciably. Despite these mammoth problems, testimonies to the linguistic and cultural affinities between Ethiopia and Arabia are evident; illustrations of which are given in this article. They could be used as a springboard for improving relations between the two communities. The Ethiopian socio-political climate has improved since the installation of a new federal and democratically elected government. It behoves all relevant groups to grasp the mettle by doing more intensive and extensive research in topics like this one in order to trace commonalities between them.